What Value Does the Pharmaceutical Industry Bring to Health Care?. (May 2015) - Laws, David
It is very rare indeed for an industry to successfully push back against the tide and resist a changing business environment, and rarer still for it to continue to be profitable through those turbulent times. In many ways the pharmaceutical industry is unique. It has indeed managed to maintain, even grow its profitability during a period of unprecedented change and uncertainty. The forces at play are significant and varied and apply across all of health care yet the notion of 'value' stands out as a key-driving concept. Pharma has typically relied on 'science' and 'product innovation around the pill' as the focus for the value they deliver but this is fast becoming not enough.With health care as a whole struggling to adapt to this new, changing environment how will big pharma respond. Change does not come easily to this powerful behemoth and with so much money at risk the pharma industry will no doubt seek to focus on maintaining the status quo.